A COMPREHENSIVE STRUCTURAL MODEL OF ONLINE/WEBSITE EXPERIENCE - Zulfahmi Zulfahmi; Radeswandri Radeswandri; Hubertina Ngarbingan; Ginta Ginting (International Journal of Applied Business and International Management, 2022)
This study evolves a model using the concept of variable flow based on the limited outcome of empirical studies regarding digital experience on critical aspects that require a theoretical basis. Flow variables in this modeling use 3 stages, starting from independent variables (interactivity, usability, connectedness, challenge, skill, telepresence, walfare), component variables (functionality, psychological, content/promoting) and outcome variables (satisfaction, belief, and behavior). The unit of analysis is website users of various tourist destinations based on local culture and traditions, with a total of 364 respondents. Data were analyzed using Structural Modeling Approach (SEM-Partial Least Square). The research model can prove most of the hypothesis testing as many as 15 of the 19 proposed hypothesis. The modeling in this study can be declared valid to be developed in the next research. There are four hypothesis analysis present insignificant results: 1) the influence of connectedness on usability; 2) the impact of content on manners determination; 3) conceptual influence on belief and, 4) influence of aptitude on psychology. For the development of future research, it is necessary to develop a more comprehensive "flow experience" model by considering the relationship of insignificant variables by considering several important things: respondent characteristics, similarity of tourist destinations and conducting comparative studies with equivalent units of analysis. Keywords: flow variable,  web/online experience, antecedents, outcome, structural.